1992
DOI: 10.1111/j.1365-2133.1992.tb00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous plasmacytoma: treatment with intralesional tumour necrosis factor-α

Abstract: We report a case of primary multiple cutaneous plasmacytomas. without underlying multiple myeloma, treated with intralesional tumour necrosis factor-a (TNF-a). A marked reduction in tumour size, with no signiHcant adverse effects, suggests that intralesiona! TNF-a is an eflective treatment for non-solid malignant tumours. Extramedullary plasmacytoma. especially involving the skin as a primary site, has rarely been reported in the Hnglish literature. We describe the ninth reported case of tnultiple cutaneous pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“… found intralesional tumor necrosis factor‐α reduced tumor size in a patient with multiple cutaneous plasmacytomas; however, lesion size did not change after the fourth injection. Oral cyclophosphamide and prednisolone were used subsequently, which reduced the tumor size and recurrence . Follow‐up is imperative in PCP.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“… found intralesional tumor necrosis factor‐α reduced tumor size in a patient with multiple cutaneous plasmacytomas; however, lesion size did not change after the fourth injection. Oral cyclophosphamide and prednisolone were used subsequently, which reduced the tumor size and recurrence . Follow‐up is imperative in PCP.…”
Section: Discussionmentioning
confidence: 88%
“…6,13,21 Risk factors for a poor prognosis include multiple lesions, tumor size > 5 cm, IgA-secreting tumors, and a compromised immune system. 5,18,21 Tsuboi et al 22 found intralesional tumor necrosis factor-a reduced tumor size in a patient with multiple cutaneous plasmacytomas; however, lesion size did not change after the fourth injection. Oral cyclophosphamide and prednisolone were used subsequently, which reduced the tumor size and recurrence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Single nodules can be resected, but plasmacytomas are radiosensitive, and electron beam radiotherapy is effective for large or deep lesions 4,5 . Other treatments tried include intralesional steroid and tumour necrosis factor‐α 10,11 . In the presence of extensive involvement, often with underlying marrow involvement, chemotherapy in conjunction with radiotherapy remains the treatment of choice 5,7 , 8 .…”
Section: Reportmentioning
confidence: 99%
“…4,5 Other treatments tried include intralesional steroid and tumour necrosis factor-a. 10,11 In the presence of extensive involvement, often with underlying marrow involvement, chemotherapy in conjunction with radiotherapy remains the treatment of choice. 5,7,8 Adjuvant a-interferon has been tried as primary treatment 12 but also following relapsed myeloma after an autologous stem cell transplant.…”
Section: Reportmentioning
confidence: 99%